OBM Neurobiology 2021
DOI: 10.21926/obm.neurobiol.2101082
|View full text |Cite
|
Sign up to set email alerts
|

Medical Hypothesis: Deep Brain Stimulation for Intractable Migraine

Abstract: Deep Brain Stimulation (DBS) has been introduced as an innovative treatment for several neurological disorders, including Parkinson’s disease, essential tremor, and dystonia and it has been proven effective in helping individuals affected by these disorders; hence, enhancing their quality of life. DBS has also been investigated for the treatment of cluster and other primary headaches. Electrodes are surgically implanted into brain structures, for example the posterior hypothalamus in case of cluster headache. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 111 publications
(167 reference statements)
0
5
0
Order By: Relevance
“…Given migraine has analogous features, it was hypothesized that it could be effective in chronic migraine. 1 The indirect positive effect on migraine after targeting the subthalamic nuclei with DBS can be explained by several possibilities. Functional MRI and positron emission tomography (PET) shows activation and hyper-perfusion of the hypothalamus in chronic migraine.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Given migraine has analogous features, it was hypothesized that it could be effective in chronic migraine. 1 The indirect positive effect on migraine after targeting the subthalamic nuclei with DBS can be explained by several possibilities. Functional MRI and positron emission tomography (PET) shows activation and hyper-perfusion of the hypothalamus in chronic migraine.…”
Section: Discussionmentioning
confidence: 99%
“…Neuromodulation with DBS might alleviate headache by improving these pathways (Figure 2). 1 In addition to calcitonin gene related peptide (CGRP) and serotonin 5-HT, dopamine has been suggested to play a key role in the pathogenies of migraine through activation of the trigeminocervical complex. 9 Cubo et al found that patients with Parkinson's disease and migraine show better clinical response in motor symptoms compared to those without migraine.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations